TOC1: A valuable tool in assessing disease progression in the rTg4510 mouse model of tauopathy - Ward, Sarah M. (2014)
All tauopathies result in various forms of cognitive decline and neuronal loss. Although in some diseases, tau mutations appear to cause neurodegeneration, the toxic “form” of tau remains elusive. Tau is the major protein found within neurofibrillary tangles (NFTs) and therefore it seemed rational to assume that aggregation of tau monomers into NFTs was causal to the disease process. However, the appearance of oligomers rather than NFTs coincides much better with the voluminous neuronal loss in many of these diseases. In this study, we utilized the bigenic mouse line (rTg4510) which conditionally expresses P301L human tau. A novel tau antibody, termed Tau Oligomer Complex 1 (TOC1) was employed to probe mouse brains and assess disease progression. TOC1 selectively recognizes dimers/oligomers and appears to constitute an early stage marker of tau pathology. Its peak reactivity is coincident with other well-known early stage pathological markers such as MC1 and the early-stage phospho-marker CP13. TOC1’s reactivity depends on the conformation of the tau species since it does not react with monomer under native conditions, although it does react with monomers under SDS-denaturation. This indicates a conformational change must occur within the tau aggregate to expose its epitope. Tau oligomers preferentially form under oxidizing conditions and within this mouse model, we observe tau oligomers forming at an increased rate and persisting much longer, most likely due to the aggressive P301L mutation. With the help of other novel antibodies, the use of this antibody will aid in providing a better understanding of tau toxicity within Alzheimer’s disease and other tauopathies.